APPROBATING METHODOLOGY FOR REDUCTION OF BODY FAT WITH CRYOLIPOLYSIS AND CAVITATION - Mariya Gramatikova; Stamenka Mitova; Iliya Kanelov (Peytchinski Publishing, 2020)
The aim of this study is to develop and approbation methods and algorithms for reducing body fat. Material/Methods: In the research, participants were aged 35-45 years with obesity. Anthropometric parameters were analyzed with an impedance analyzer for bodyweight parameters, a somatotype profile, by the methodology Heath-Carter. Measurements were made before and after 60 days of the apparatus physiotherapy including cryolipolysis and cavitation. Twice a week a cardio training was performed Results: The somatotype of the contingent is Mesomorphic - endomorphic endomorphism is highest (6.63), and mesomorphic (6.36) is higher than ectomorph (1.08). In the second study, the data showed a decrease in the endomorphic index (6,18), having almost equalized values with the mesomorph (6,15), while at the same time the greatest movement was observed in the ectomorphic index, which increased with nearly 30% to 1.38. The research contingent has positively influenced the procedures and its propensity for weight loss has increased. However, the somatotype profile remains a mesomorph-endomorph. From the data on the quality of the body composition, only the BMI (kg/m2), VFA (cm2) and MBF (kg) parameters have statistically significant decreases. The measured parameters before and after the applied procedures, with no statistically reliable changes P-value <0.05 level (Wilcoxon, t-test) observed only in the circumference of the hips. A statistically significant decrease of the results is found in the circumferences of both thighs at the measured heights P-value <0.0 001 level (Wilcoxon, t-test). Conclusion: The approbation methodology for reducing body fat has a positive effect on the contingents and leads to the modeling of the body.